(untitled) (International Journal of Engineering and Computer Science, 2017)
Weather conditions i.e. rain, snow, fog, mist and haze degrade the quality also performance of outdoor vision system. Rain is one of the type of weather condition as well as rain is the major component for the dynamic bad weather. Rain introduces sharp intensity variations in images, which degrade the quality or performance of outdoor vision systems. These intensity variations depend on various factors, such as the brightness of the scene, the properties of rain, and the camera parameters. Rain removal has many applications in the field of security surveillance, vision based navigation, video or movie editing and video indexing or retrieval. So, it is important to remove rain streaks from the images. The detection and removal of rain streaks in an image is done by image decomposition which depends on Morphological Component Analysis (MCA) by performing dictionary learning and sparse coding. Rain streaks removal is fall into the category of image noise reduction. After Removal of rain streaks we can easily identify feature in the image